Complications of Ponseti Technique in Treatment of Idiopathic Club Foot - Redah, Samer Mohammed (AL-Kindy College Medical Journal, 2022)
Background: Clubfoot, or talipes equinovarus, is a congenital deformity that consist of; supination and adduction of the forefoot and midfoot; equinus of hindfoot and varus. It was found that more than 100,000 babies are born each year with congenital clubfootObjectives: The purpose of this study was to investigate the complications of  ponseti method for treatment of children with idiopathic club foot.Subjects and Methods: 50 children with 74 clubfeet were managed by Ponseti method from May 2019 to July 2020 in Al-Wasity teaching hospital with primary correction of the deformity followed sometimes by elongation of Achilles tendon then the patients were followed up till June 2021 and the complications were calculated.Results: complications were  10.8%  incomplete correction (mostly equinus) and it was corrected by surgery, 6.7%  ulcer on the medial surface of head of 1st metatarsal , 9.4%  cast falling and 18.9%  relapse.Conclusions:  Ponseti technique is a safe and effective method for correction of  clubfoot and decreases the need for corrective surgery with minimal complications that can be easily managed.